Religious Moderation in the History of the Indonesian Nation - Mailin, Mailin; Alfiansyah, Raja; Lie, Alvin; Juha, Alwi Auvinen; Haramain, Sultan (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
This study aims to analyze the values of Religious Moderation in the historical trajectory of the Indonesian Nation. The beginning of the establishment of the Unitary State of the Republic of Indonesia began when the Proclamation of Indonesian Independence was read on August 17, 1945. Indonesia has an archipelago spread with a variety of customs, cultures, tribes, and beliefs.┬á This diversity coexists peacefully, but lately, the Indonesian nation has experienced a crisis of heterogeneity. This is evidenced by several cases of intolerance, extremism, destruction of houses of worship and so on. Ideally, the predecessors of the Indonesian nation upheld the values of religious moderation which are now fading. The urgency of this research is to form an ideal understanding of religious moderation through historical values. This research uses qualitative methods with a history-based phenomenological approach. The primary data sources in this study are historical evidence, while the secondary data used are books, articles and reports that support the research. Data will be analyzed using Triangulation, Member Checking, and Conclusion Drawing techniques. The results showed that in terms of history the Indonesian nation has upheld the values of tolerance, harmony, and non-violence. This can be seen from the adoption of the Sutasoma book which became the basic foundation of the state and Pancasila as a moral instruction that contains philosophical values. Local wisdom in society has the value of religious moderation. The government in this case has made efforts through, training on strengthening Religious Moderation for the community, interfaith dialogue, the role of mass media, and government supp